If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = -2(2x + 4) Reorder the terms: 4x = -2(4 + 2x) 4x = (4 * -2 + 2x * -2) 4x = (-8 + -4x) Solving 4x = -8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4x + 4x = -8 + -4x + 4x Combine like terms: 4x + 4x = 8x 8x = -8 + -4x + 4x Combine like terms: -4x + 4x = 0 8x = -8 + 0 8x = -8 Divide each side by '8'. x = -1 Simplifying x = -1
| x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k | | (2/3)x-(1/6)=(2/7) | | d=85t+340 | | 3(3*x+4*y+5)+2(2*x-4*y-3)=z | | 2x=4x+18 | | 6-5(3x-2)=-14 | | X+.25X=45 | | 16x-5=2(2x+3) | | -149=10x-29 | | 4/(-1)-5 | | 6=(y-10) | | 4/(-1) | | (3x-2/4)+(x+57/7)=13 | | x4/x=2 | | 30=90/x | | (9-2y)/3=y | | 6-6r-2=16 | | 30=90 | | 3(3*x+4*y+5)+2(2*x-4*y-3)= | | 3x-2/4+x+57/7=13 | | 1.8z-1(-2+z)=1.5 |